2017
DOI: 10.1103/physrevd.95.014018
|View full text |Cite
|
Sign up to set email alerts
|

Parton shower uncertainties in jet substructure analyses with deep neural networks

Abstract: Machine learning methods incorporating deep neural networks have been the subject of recent proposals for new hadronic resonance taggers. These methods require training on a dataset produced by an event generator where the true class labels are known. However, this may bias the network towards learning features associated with the approximations to QCD used in that generator which are not present in real data. We therefore investigate the effects of variations in the modelling of the parton shower on the perfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 62 publications
2
141
0
Order By: Relevance
“…This distinguishes our approach from tagging methods which use Monte Carlo simulations for training, like the Template Tagger [9][10][11][12]. This means that for our performance test we do not have to include uncertainties in our Pythia simulations compared to other Monte Carlo simulations and data [51].…”
Section: Jhep05(2017)006mentioning
confidence: 99%
“…This distinguishes our approach from tagging methods which use Monte Carlo simulations for training, like the Template Tagger [9][10][11][12]. This means that for our performance test we do not have to include uncertainties in our Pythia simulations compared to other Monte Carlo simulations and data [51].…”
Section: Jhep05(2017)006mentioning
confidence: 99%
“…The image-based approach has been extensively studied for various jet tagging tasks, e.g., W boson tagging [25][26][27][28][29]35], top tagging [32][33][34] and quark-gluon tagging [30,31]. Convolutional neural networks (CNNs) with various architectures were explored in these studies, and they were found to achieve sizable improvement in performance compared to traditional multivariate methods using observables motivated by QCD theory.…”
Section: Image-based Representationmentioning
confidence: 99%
“…The implementation details can be found in Appendix A. Note that the ResNeXt-50 architecture is much deeper and therefore has a much larger capacity than most of the CNN architectures [25,[27][28][29][30][31][32][33][34][35] explored for jet tagging so far, so evaluating its performance on jet tagging will shed light on whether architectures for generic image classification is also applicable to jet images.…”
Section: Top Taggingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent development of these simulations has seen improvements in various areas, both within perturbative calculations, through matching to fixed order [2,[7][8][9][10][11][12][13][14][15], combining higher jet multiplicities [16][17][18][19][20][21][22], as well as the all-order resummation with parton showers [23][24][25][26] and also within the non-perturbative, phenomenological models [27,28]. While there are well established prescriptions on how to quantify the theoretical uncertainty of fixed-order calculations due to missing higher-order contributions [29][30][31][32][33][34][35] 1 , there is no such consensus for general resummed calculations [36][37][38][39][40][41], and parton-shower algorithms in particular [42][43][44][45][46][47], since a number of ambiguities are present within the different schemes; however, there is progress in towards this goal. Given the perturbative improvements, and the expected precision from data-taking at Run II of the Large Hadron Col- …”
Section: Introductionmentioning
confidence: 99%